Function and mechanism of histone β-hydroxybutyrylation in health and disease - Zhou, Tingting; Cheng, Xi; He, Yanqiu; Xie, Yumei; Xu, Fangyuan; Xu, Yong; Huang, Wei (Frontiers in Immunology, 2022)
Histone post-translational modifications (HPTMs) are essential epigenetic mechanism which affect chromatin-associated nuclear processes without altering the DNA sequence. With the application of mass spectrometry-based proteomics, novel histone lysine acylation, such as propionylation, butyrylation, crotonylation, malonylation, succinylation, glutarylation, and lactoylation have been successively discovered. The emerging diversity of the lysine acylation landscape prompted us to investigate the function and mechanism of these novel HPTMs in health and disease. Recently, it has been reported that β-hydroxybutyrate (BHB), a main component of ketone body, has various protective roles beyond alternative fuel provision during starvation. Histone lysine β-hydroxybutyrylation (Kbhb) is a novel HPTMs identified by mass spectrometry, which regulate gene transcription in response to carbohydrate restriction or elevated BHB levels in vivo and vitro. Recent studies have shown that histone Kbhb is strongly associated with the pathogenesis of metabolic cardiovascular diseases, kidney disease, tumors, and neuropsychiatric disorders, suggesting it has different functions from histone acetylation and methylation. This review focuses on the writers, erasers, sites, and underlying functions of histone Kbhb, providing a glimpse into their complex regulation mechanism.